A Brief History of the Teacher Behavior Checklist. (12th July 2018) - Kirby, Lauren A. J.; Busler, Jessica N.; Keeley, Jared W.; Buskist, William
Abstract: We summarize the history of the development of the Teacher Behavior Checklist and review examples of its utility for studying excellence in teaching across cultures and contexts.